1989
DOI: 10.1121/1.397755
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic, acoustic, and perceptual analyses of connected speech produced by Parkinsonian and normal geriatric adults

Abstract: Acoustic and kinematic analyses, as well as perceptual evaluation, were conducted on the speech of Parkinsonian and normal geriatric adults. As a group, the Parkinsonian speakers had very limited jaw movement compared to the normal geriatrics. For opening gestures, jaw displacements and velocities produced by the Parkinsonian subjects were about half those produced by the normal geriatrics. Lower lip movement amplitude and velocity also were reduced for the Parkinsonian speakers relative to the normal geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
164
1
19

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 0 publications
13
164
1
19
Order By: Relevance
“…Through this test, several authors 12,14,15 found a reduction of the displacement and of the peak velocities of lower lip and jaw during the opening and the closing of the mouth. A slowdown of jaw and lower lip movements was demonstrated also by Forrest et al 13 ; on the other hand, they found an increase of the closing velocity of the lower lip in PD patients. This result might reflect an alteration of the motion control due to the severity of the dysarthria.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Through this test, several authors 12,14,15 found a reduction of the displacement and of the peak velocities of lower lip and jaw during the opening and the closing of the mouth. A slowdown of jaw and lower lip movements was demonstrated also by Forrest et al 13 ; on the other hand, they found an increase of the closing velocity of the lower lip in PD patients. This result might reflect an alteration of the motion control due to the severity of the dysarthria.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, our work supports most of the literature on the kinematic analysis of the articulators in PD patients with hypokinetic dysarthria, which states that most of these patients exhibit a downscaling of the articulatory movements. [12][13][14][15][16]18 The novel contribution of this work concerns the assessment of this downscaling by means of a fully markerless and lowcost method. We described in detail the video-processing framework: camera calibration, face tracking, 3D coordinates estimation, and calculation of the kinematic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In articulatory kinematic analyses, measures of movement parameters (duration, displacement, and velocity) and variability (standard deviations, covariance, and the spatiotemporal index (STI)), have been utilized to study normal speech production, changes to speech production with development or normal aging, and changes to speech production in individuals with motor disorders (Ackermann, Hertrich, Daum, Scharf, & Spieker, 1997;Ackermann, Hertrich, & Scharf, 1995;Dromey, Ramig, & Johnson, 1995;Forrest, Weismer, & Turner, 1989;Green, Moore, Higashikawa, & Steeve, 2000;Kleinow, Smith, & Ramig, 2001;McClean & Tasko, 2003;Perkell, Matthies, Svirsky, & Jordan, 1993;Schulman, 1989;Smith, Goffman, Zelaznik, Ying, & McGillen, 1995;Tasko & McClean, 2004;Wohlert & Smith, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other deviations were reported always in acoustic studies: the reduced duration of formant transitions (Connor et al 1989;Forrest et al, 1989), the voicing of voiceless consonants assigned to the rigidity of the larynx, a control loss of voice onset time (VOT), that is to say, the time between the release of the consonant and the beginning of voicing, resulting in a lack of coordination between the larynx and articulatory organs (Forrest et al, 1989;Lieberman et al, 1992).…”
Section: Other Anomaliesmentioning
confidence: 99%